New 1-hydroxy-2-thiopyridine derivatives active against both replicating and dormant Mycobacterium tuberculosis. Issue 11 (November 2017) - Salina, Elena G.; Ryabova, Olga; Vocat, Anthony; Nikonenko, Boris; Cole, Stewart T.; Makarov, Vadim
Abstract: Tuberculosis (TB) treatment is confounded by the range of metabolic states displayed by Mycobacterium tuberculosis, by the long duration required and by the increasing prevalence of drug-resistant strains. Latent TB infection is especially difficult to treat due to the phenotypic antibiotic resistance of non-replicating M. tuberculosis . Therefore, the development of new drugs effective against both active and latent TB infection is needed. New 1-hydroxy-2-thiopyridine derivatives were synthesized and found to be highly effective in vitro against both actively growing and dormant non-culturable M. tuberculosis . Such compounds are leads for the development of new drugs for all forms of TB including latent infection.